2022
DOI: 10.1001/jamainternmed.2022.4924
|View full text |Cite
|
Sign up to set email alerts
|

Association Between US Drug Price and Measures of Efficacy for Oncology Drugs Approved by the US Food and Drug Administration From 2015 to 2020

Abstract: This cross-sectional study estimates all US Food and Drug Administration anticancer approvals in recent years and evaluates if an association exists between their cost and efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 6 publications
1
5
0
2
Order By: Relevance
“…Unlike US or Europe, monthly prices in Canada significantly differed for cancer drugs with substantial benefit vs low benefit per MCBS scores. However, consistent with other studies, 1 , 2 there was only a weak correlation between monthly drug prices and PFS or OS gains.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Unlike US or Europe, monthly prices in Canada significantly differed for cancer drugs with substantial benefit vs low benefit per MCBS scores. However, consistent with other studies, 1 , 2 there was only a weak correlation between monthly drug prices and PFS or OS gains.…”
Section: Discussionsupporting
confidence: 91%
“…
Cancer drug prices have increased exponentially in the past decade and several studies have demonstrated an increasing disconnect between clinical benefit and prices for cancer drugs approved by the US Food and Drug Administration or the European Medicines Agency. 1,2 This disconnect seemed to exist even in the setting of central price negotiations in Italy. 3 However, to our knowledge this has not been studied for Canada.
…”
mentioning
confidence: 99%
“…However, evidence has shown the contrary. In a 2022 analysis, the median annual cost of drugs approved based on improvement in overall survival was the lowest of the 3 end points, indicating that factors other than novelty play an important role in drug pricing. It also found that among the drugs approved on the basis of response rate, there was a weak correlation between cost and the magnitude of that gain in response rate, and the same was true in the categories of drugs approved on the basis of gains in progression-free and overall survival …”
Section: Discussionmentioning
confidence: 99%
“…Looking at the prevalence of such innovation in anticancer drugs, a previous study found 332 new drug approvals over 12 years, with 53 (16%) having a novel mechanism of action, 84 (25%) being first approval of a next in class compound, and 195 (59%) being subsequent approvals of the same drug. A similar study also found drug approvals from 2015 to 2020 showing weak correlation between clinical benefit and pricing.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, a recent report from the United States did not find a link between measures of benefit and the price for drugs that treat cancer. Oncology drugs approved on the basis of overall survival improvement had a lower median price than drugs approved using surrogate end points such as progression-free survival or overall response rate (Miljković et al 2022). This finding about the (non-)relationship between benefits and pricing is especially concerning since (based on my unpublished research) 52 of the 61 new oncology drugs approved in Canada between 2015 and 2020 used surrogate outcomes.…”
Section: Introductionmentioning
confidence: 99%